FORMULASI SALEP EKSTRAK METANOL DAUN SRIKAYA (Annona squamosa L) DENGAN BERBAGAI VARIASI BASIS - Muflihunna, A. (Jurnal Ilmiah As-Syifaa, 2009)
This research methanol extract srikaya leaf performed to formulate ointments in bases variation that were hydrocarbon base, absorption base, water-soluble and emultion base. The aim was to determine which one the most stable base contain the methanol extract srikaya leaf. Stability evaluation maked in two condition were before and after stress condition at 5oC â€“ 35oC for 10 cycles, by which the parameters were organoleptic observation, viscosity measurement, and yield value determination. Result of organoleptic showed that there was not alteration in color, smell, and consistency of those four bases, before and after stress conditioned. Statistyc data analyse of viscosity measurement showed that formula in absorption base was the stable one due to no alteration before and after accelerated condition. Yield value showed that there was thixotrophy plastic flowing exhibited by rheogram. And of those four formula ointment types of methanol extract srikaya leaf (Annona squamosa L) that have been made in, absorption base was the most stability optimum base.Â Key words: srikaya leaf, ointment, formulation